Assessing the Probability of Industrial Workers Entering High-Productivity Clusters: A Probit Analysis of Digital Technology and Training - Nilam Yuliawati; Wildan Syafitri; Dias Satria (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The labor productivity of the manufacturing sector in East Java remains 7.6% below the national average, despite the province’s substantial contribution to the national Gross Domestic Product (GDP). This disparity reflects structural challenges in the transformation of workers’ digital capabilities, particularly because digitalization does not necessarily generate homogeneous effects on productivity. This study aims to assess the probability of manufacturing workers entering high-productivity clusters by emphasizing the multidimensional roles of digital technology and job training. Utilizing microdata from the August 2025 National Labor Force Survey (Sakernas) comprising 3,200 workers, this study employs a Binary Probit model with Average Marginal Effects (AME) as the primary basis for interpretation, complemented by diagnostic tests including Variance Inflation Factor (VIF), link test, Wald test, and Receiver Operating Characteristic (ROC) curve analysis. The findings indicate that digital economy adoption is the most dominant determinant of productivity, exhibiting the largest marginal effect (+21.13 percentage points), followed by digital device adoption (+8.77 percentage points). In contrast, digital information literacy significantly reduces the probability of entering high-productivity clusters (-6.79 percentage points). Job training demonstrates a positive direction but does not have a statistically significant effect (+3.35 percentage points). The model exhibits adequate discriminatory performance with an Area Under the Curve (AUC) value of 0.7527 and an overall classification accuracy of 69.19%. These findings confirm that digitalization is not a homogeneous phenomenon; different dimensions of digital capability generate distinct structural effects on workers’ productivity stratification. Therefore, industrial firms should prioritize the enhancement of digital economy capabilities as a strategic human capital investment. Furthermore, the government needs to shift its digitalization policy focus from merely providing infrastructure toward structured digital skills development programs that are more relevant to the manufacturing sector.